محددات القومية في فكر ساطع الحصري وانعكاساتها على المواطنة - حاروش, نورالدين (جامعة الوادي University of Eloued, 2019)
محددات القومية في فكر ساطع الحصري وانعكاساتها على المواطنة The determinants of nationalism in the thought of Shati Al- Husri and its implications on citizenship بادر بعض المفكرين العرب والمسلمين لإعادة بعث الأمة الإسلامية ونهضتها من جديد بداية من القرن التاسع عشر ميلادي، ملامح هذه النهضة أو لنقل اليقظة تمثلت في اتجاهات فكرية مختلفة، وسنقوم في هذه الدراسة بالتركيز على الاتجاه القومي الذي تبناه وبدون منازع ساطع الحصري، وعليه فهذه الورقة البحثية تهدف إلى تسليط الضوء على موضوع غاية في الأهمية قديما وحديثا، كونه لا يزال يشغل بال المفكرين والفلاسفة العرب خاصة إلى يومنا هذا ويتعلق الأمر بمسألة القومية العربية في فكر ساطع الحصري وعلاقتها بالدين والوطن والوطنية والمواطنة وتكوين الدولة. Some Arab and Muslim thinkers initiated the re-awakening of the Islamic Ummah from the 19th century, The features of this renaissance or of vigilance were represented in different intellectual directions, In this study, we will focus on the national trend adopted uncontestedly by Shati Al-Husri. This paper aims to shed light on a subject of great importance in ancient and modern times, as it is still preoccupied with especially Arab thinkers and philosophers to this day. It concerns the issue of Arab nationalism in the thought of Shati Al-Husri, and its relation with religion, homeland, patriotism, citizenship and state formation.
The Determinants Of Nationalism In The Thought Of Shati Al- Husri And Its Implications On Citizenship
Keywords: ساطع الحصري، القومية، الأمة، اللغة، التاريخ، المواطنة; Shati Al-Husri ,national, nation, language, history, citizenship.